Key aspects of the primary sex determination mechanism are conserved across the genus Drosophila. - Erickson, J.W.; Cline, T.W. (Development, 1998)
In D. melanogaster, a set of 'X:A numerator genes', which includes sisterlessA (sisA), determines sex by controlling the transcription of Sex-lethal (Sxl). We characterized sisA from D. pseudoobscura and D. virilis and studied the timing of sisA and Sxl expression with single cell-cycle resolution in D. virilis, both to guide structure-function studies of sisA and to help understand sex determination evolution. We found that D. virilis sisA shares 58% amino acid identity with its melanogaster ortholog. The identities confirm sisA as an atypical bZIP transcription factor. Although virilis sisA can substitute for melanogaster sisA, the protein is not fully functional in a heterologous context. The putative sisA regulatory sequence CAGGTAG is a potential 'numerator box,' since it is shared with the other strong X:A numerator gene, sisB, and its target, SxlPe. Temporal and spatial features of sisA and SxlPe expression are strikingly conserved, including rapid onset and cessation of transcription in somatic nuclei, early cessation of sisA transcription in budding pole cells and persistent high-level sisA expression in yolk nuclei. Expression of sisA and Sxl is as tightly coupled in virilis as it is in melanogaster. Taken together, these data indicate that the same primary sex determination mechanism exists throughout the genus Drosophila.